Development of an Eco-Friendly Bio-Battery Using Cucumber and NaCl as Ion Sources and Tapioca Flour as a Matrix - Widyaningsih, Fitria; Atina; Rahman, Dui Yanto (Jurnal Penelitian Fisika dan Terapannya (JUPITER), 2025)
The use of natural materials in bio-battery research plays a crucial role in the search for environmentally friendly and cost-effective energy solutions. This study aims to determine the optimal composition of fermented cucumber juice and the addition of NaCl at the fermentation's optimal point to produce maximum current and voltage. Graphite sheets were used as the anode and aluminum sheets as the cathode. The cucumber juice was fermented for varying durations: 0, 24, 48, 72, 96, 120, 144, and 168 hours. Tapioca flour was gradually added until a solid electrolyte was formed. This solid electrolyte was then placed between the graphite and aluminum sheets to measure current and voltage output. At the optimal fermentation time, varying amounts of NaCl (0.5 g, 1 g, 1.5 g, 2 g, 2.5 g, and 3 g) were added to determine the best-performing composition. The results showed that the optimal composition without NaCl was achieved at 48 hours of fermentation, yielding a current of 0.76 mA and a voltage of 0.695 V. With the addition of NaCl, the maximum current and voltage reached 2.01 mA and 0.704 V, respectively, with the optimal NaCl mass being 1.5 g. This research shows great promise for further development due to its simple methodology and the use of low-cost, eco-friendly materials.